Language of instruction and its effect on the performance of accounting students - Rossouw, M. (South African Journal of Higher Education, 2018)
Aspiring CA (SA)’s have to pass two professional exams in order to register as a member with SAICA and become a CA (SA). These exams are available in Afrikaans and English. Subsequently, some South African universities offer Accounting programmes in one of these languages. Afrikaans students are faced with the choice of receiving instruction in their home language or in English – the language of the business world. The objective of this study was to investigate language of instruction and its effect on performance for Afrikaans Accounting students. Afrikaans students who receive instruction in English were compared to their counterparts, who receive instruction in their home language. Questionnaires were distributed to obtain students’ school and university results, and to gather opinions on matters affecting the decision about language of instruction. It was found that, among Afrikaans students, home-language instruction leads to marginally better mid-year results at tertiary level.